Treatment of irreducible atlantoaxial dislocation using one-stage retropharyngeal release and posterior reduction. (23rd August 2019) - Ren, Xianfeng; Gao, Feng; Li, Siyuan; Yang, Jiankun; Xi, Yongming
Introduction: Irreducible atlantoaxial dislocation (IAAD) has been challenging for spine surgeons. Various methods have been used to treat IAAD, but no consensus has been reached. This study aimed to retrospectively analyze the efficacy of anterior submandibular retropharyngeal release and posterior reduction and fixation for IAAD. Methods: From March 2007 to May 2015, 13 patients diagnosed with IAAD underwent anterior submandibular retropharyngeal release and sequential posterior reduction and fixation. The operation time, blood loss, postoperative complications, and Japanese Orthopaedic Association (JOA) scores were retrospectively recorded. Results: The surgeries were accomplished successfully. The mean operative time was about 3.8 h. The mean estimated blood loss was about 130 mL. The patients experienced postoperative pharyngeal pain. Only one patient had a vague voice and increased oral discharge postoperatively. At the final follow-up, JOA scores had significantly increased ( p < 0.05), and all the patients had solid bony fusion. Conclusion: The present study reinforces the efficacy and safety of anterior submandibular retropharyngeal release and posterior reduction and fixation for IAAD. It can achieve satisfactory clinical outcomes and is safe for experienced spine surgeons.